B because 3*3=9 And 3*1=3 so it would be 3(3y-1) foil the answer
The man is 27 years old and the son is 9 years old.
We can write the son's age as 'x', and therefore write the man's age as 4x. In 3 years, both their ages will increase by 3, so the son's age is now x + 3, and the man's age is 4x + 3.
We are told that the man is now 3 times older than his son, which means his current age, 4x + 3, is the same as 3 times the son's current age, which is x + 3.
Therefore we can write an equation:
4x + 3 = 3(x + 3)
4x + 3 = 3x + 9
- 3x
x + 3 = 9
- 3
x = 6
We can now substitute this in to find their current ages:
Son's age = x + 3 = 6 + 3 = 9
Man's age = 4x + 3 = 24 + 3 = 27
I hope this helps! Let me know if you have any questions :)
Using the logarithm base (8) on the right side to equal the exponent.
The answer would be D. log8 (1/8) = -1
Answer:c
Step-by-step explanation:
Answer:
B
Step-by-step explanation:
............................................